Timing estimation of multiple hyperbolic frequency‐modulated signals based on multicarrier underwater acoustic communication. Issue 12 (22nd August 2022) - Cui, Xuerong; Yan, Peihao; Li, Juan; Zhang, Hao; Li, Shibao; Liu, Jianhang
Abstract: Underwater acoustic channel is much more complex than radio channel. Background noise, multipath extension, and Doppler frequency shift are all factors that affect high‐speed and stability for underwater communication. Orthogonal frequency division multiplexing (OFDM) is a modulation technology with high spectrum efficiency and strong anti‐multipath ability, usually used in high‐speed underwater acoustic communication. Signal arrival time detection and timing estimation before receiving data is an essential module in an underwater communication system. Timing estimation error will seriously affect the demodulation of the signal. In order to solve the problem of a complex channel environment in underwater acoustic communication system, a timing estimation method is proposed based on multiple hyperbolic frequency‐modulated (MHFM) signals. In order to improve the performance of underwater acoustic communication systems, this article proposes an iterative method of correlation‐sum‐mean absolute error (MAE) based on hyperbolic frequency‐modulated (HFM). The simulation results show that the proposed method can provide better performance and higher timing estimation accuracy under the conditions of low signal‐to‐noise ratio (SNR) and Doppler effect under oceanic noise channel and Doppler spread channel. Abstract : In order to solve the problem of a complex channel environment in underwater acoustic communication system, a timing estimation method of correlation‐sum‐mean absolute error (MAE) is proposed based on multiple hyperbolic frequency‐modulated (MHFM) signals. It estimate signal arrival time for symbol synchronization. The simulation results show that the proposed method can provide better performance and higher time estimation accuracy under the conditions of low signal‐to‐noise ratio (SNR) and Doppler effect.